2016
DOI: 10.1128/iai.00584-16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Moderate Temperature Changes on Neisseria meningitidis Adhesion Phenotypes and Proteome

Abstract: bNeisseria meningitidis, the meningococcus, bears the potential to cause life-threatening invasive diseases, but it usually colonizes the nasopharynx without causing any symptoms. Within the nasopharynx, Neisseria meningitidis must face temperature changes depending on the ambient air temperature. Indeed, the nasopharyngeal temperature can be substantially lower than 37°C, the temperature commonly used in experimental settings. Here, we compared the levels of meningococcal biofilm formation, autoaggregation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Lipooligosaccharide (LPS) electrophoresis was used to compare the LPS pattern between throat and corresponding blood isolates and was carried out as described in [56]. Briefly, bacteria were grown over night on Columbia blood agar plates (bioMérieux).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipooligosaccharide (LPS) electrophoresis was used to compare the LPS pattern between throat and corresponding blood isolates and was carried out as described in [56]. Briefly, bacteria were grown over night on Columbia blood agar plates (bioMérieux).…”
Section: Methodsmentioning
confidence: 99%
“…After electrophoresis, gels were stained by silver staining as described in ref. [56] and photographed using a Bio-Rad ChemiDoc MP imaging system.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant NHBA-derived C2 fragment exerts a toxic effect on endothelial cells altering endothelial permeability [ 9 ]. The recent finding that NHBA protein is more expressed and cleaved at lower temperatures than 37°C [ 12 ], which are temperatures encountered during N . meningitidis initial colonization of the upper respiratory tract, led us to hypothesize that C2 fragment could also alter the epithelial permeability and facilitate the traversal of N .…”
Section: Resultsmentioning
confidence: 99%
“…Since NHBA expression is upregulated at 32°C [ 12 ], a temperature encountered during N . meningitidis initial colonization of the upper respiratory tract [ 13 ], we hypothesized that the C2 fragment could also alter the epithelial permeability and facilitate the traversal of N .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of the bacterial capsule, heparin binding mediated by NHBA is associated with increased survival of N. meningitidis in human serum and might facilitate adherence to host tissues by binding to heparan sulfate proteoglycans [35]. Recently, it has been found that NHBA expression is temperature dependent and higher at 30°C and 32°C, suggesting that NHBA might be up-regulated in the nasopharyngeal niche and be involved in the attachment to epithelial cells and colonization [81]. NHBA is recognized by sera from patients convalescing from IMD and induces SBA that correlates with the level of NHBA expression [35].…”
Section: Factor H Binding Protein (Fhbp; Gna 1870 or Lp2086)mentioning
confidence: 99%